A high-permeability selective nanofiltration membrane, a preparation method and application thereof
Patent Information
- Application Number
- CN202610693828.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-20
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-20
AI Technical Summary
中国专利CN116899419A、CN118371134B及CN119588179B等采用纳米材料构建中间层或沉积层以增强界面结合,虽能在90℃高温下保持结构稳定,但中间层的引入增加了膜厚度和传质阻力,且纳米粒子的分散均匀性难以保证,存在成膜后易脱落的隐患
[0026] (1) Pion-induced post-treatment strategy: For the first time, the characteristics of strongly hydrated ions in the Hofmeister effect were introduced into the post-treatment modification of polyamide nanofiltration membranes, and the structure-activity relationship between ion types, chain segment interactions, membrane microstructure and macroscopic properties was established, providing new theoretical guidance for the precise preparation of high-performance nanofiltration membranes.
Smart Images

Figure CN122209238B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane separation technology, specifically to a high-permeability selective nanofiltration membrane, its preparation method, and its application. Background Technology
[0002] Nanofiltration, as a pressure-driven membrane separation technology, is widely used in drinking water purification, industrial wastewater treatment, food processing, and pharmaceutical purification due to its advantages such as low operating pressure, high selectivity, energy saving, and environmental friendliness. With the continuous expansion of industrial applications, the treatment of high-temperature materials (such as dyeing and printing wastewater, food processing wastewater, and high-temperature chemical liquids) places higher demands on the temperature resistance of nanofiltration membranes.
[0003] Currently, most commercially available nanofiltration membranes use polyamide as the separation layer material and are prepared via interfacial polymerization. However, the traditional interfacial polymerization process has an extremely fast reaction rate, typically completed within tens of seconds, resulting in poor uniformity and a wide pore size distribution in the resulting polyamide separation layer. Furthermore, existing nanofiltration membranes generally suffer from a trade-off between water flux and selectivity. More importantly, at high temperatures (>60°C), the thermal motion of the polyamide chains intensifies, leading to membrane structure relaxation, increased pore size, and a significant decrease in separation performance. This deficiency severely limits the application of nanofiltration membranes in high-temperature material processing.
[0004] To overcome this bottleneck, researchers have conducted extensive studies on novel monomer development, introduction of nanomaterials, and construction of intermediate layers. For example, Chinese patent CN115672031A modulates the interfacial polymerization process by adding inorganic salts and silane additives to the aqueous phase, enabling the membrane to be used under 70°C hot water conditions. However, this method mainly focuses on intervening in the film formation process and does not involve subsequent regulation of the already formed film structure, and its long-term thermal stability needs to be verified. Chinese patents CN116899419A, CN118371134B, and CN119588179B use nanomaterials to construct intermediate or deposited layers to enhance interfacial bonding. Although they can maintain structural stability at 90°C, the introduction of the intermediate layer increases the film thickness and mass transfer resistance, and the uniformity of nanoparticle dispersion is difficult to guarantee, posing a risk of easy detachment after film formation. Chinese patent CN118491316A uses rigid amine monomers to replace traditional flexible monomers for interfacial polymerization. It leverages the characteristic that the thermal motion of rigid molecular chains is less affected by temperature to improve temperature resistance. However, the reactivity and solubility of rigid monomers differ from those of traditional monomers, requiring high process adaptability, and the resulting membrane has high density and limited throughput. Chinese patent CN119746659A constructs a rigid separation layer through the deposition of a multi-component heterocyclic conjugated polymer complex formed by the oxidative polymerization of aniline. While it exhibits strong thermal stability, it involves a multi-step reaction with strong oxidants, making the process complex and posing environmental safety risks.
[0005] In summary, existing nanofiltration membrane preparation technologies mainly suffer from the following technical bottlenecks:
[0006] Firstly, most studies focus on intervention in the interfacial polymerization process or monomer design, lacking effective means to finely control the existing film structure, making it difficult to achieve precise optimization of the film structure.
[0007] Secondly, the method of constructing intermediate or coating layers using nanomaterials has inherent problems such as complex processes (multi-step reactions, difficulty in nano-dispersion), reduced throughput due to structural thickening, and easy detachment of nanoparticles.
[0008] Third, existing modification methods generally fail to achieve a synergistic improvement in both temperature resistance and water flux, often sacrificing flux for thermal stability, or resulting in limited improvement in temperature resistance.
[0009] Fourth, some technologies involve organic solvents, strong oxidants, or complex multi-step reactions, which are not environmentally friendly and are difficult to scale up industrially.
[0010] Therefore, developing a green, simple, and scalable modification method that can precisely control the microstructure of the polyamide separation layer and simultaneously improve its temperature resistance and water flux has significant industrial and academic value. Summary of the Invention
[0011] This invention aims to address the shortcomings of existing technologies by providing a high-permeability-selectivity nanofiltration membrane, its preparation method, and its applications. The invention introduces specific ions during the post-processing stage of nanofiltration membrane preparation via interfacial polymerization. These ions, through their specific interactions with polyamide segments, induce controllable densification and ordered rearrangement of the polyamide segments, thereby achieving precise control over the microphase structure of the polyamide separation layer. After ion regulation, the polyamide segments are more regularly arranged, residual stress is reduced, and inter-chain interactions are enhanced, suppressing the thermal motion of the membrane segments at high temperatures and thus exhibiting excellent temperature stability. Finally, a nanofiltration membrane with both high permeability-selectivity and excellent temperature resistance is obtained.
[0012] To solve the above-mentioned technical problems, the present invention specifically adopts the following technical solution:
[0013] In a first aspect, the present invention provides a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0014] S1: An interfacial polymerization reaction is carried out on the surface of the base film using a polyamine aqueous solution and a polyacrylamide oil solution to form a nascent polyamide film;
[0015] S2: The nascent polyamide membrane is placed in an aqueous solution containing densification-inducing ions for heat treatment to obtain a heat-treated composite membrane; wherein, the densification-inducing ions are selected from inorganic anions and / or organic anions and cations with strong hydrogen bond acceptor or strong hydration capacity, and through non-covalent interactions with polyamide segments, regulate the microphase separation behavior of the membrane separation layer, inducing controllable shrinkage and ordered rearrangement of the segments, forming a densified and thermally stable separation layer structure; the densification-inducing ions include inorganic anions, organic anions, and cations; the inorganic anions include , , , The organic anions include formate, acetate, propionate, citrate, and tartrate; the cations include... , , , , ;
[0016] S3: After heat treatment, the composite membrane is cleaned and dried to obtain a high-permeability selective nanofiltration membrane.
[0017] Further, in step S1, the polyamine aqueous solution and the polyacrylamide oil solution are prepared by the polyamine aqueous monomer and the polyacrylamide oil monomer, respectively. The polyamine aqueous monomer includes piperazine, polyethyleneimine, and m-phenylenediamine; the polyacrylamide oil monomer includes pyromellitic tricarboxylate chloride and isophthaloyl chloride.
[0018] Furthermore, the mass ratio of the polyamine aqueous phase monomer to the polyacrylamide oil phase monomer is 0.05~60.
[0019] Further, in step S1, the base membrane is a polysulfone, polyethersulfone, polyacrylonitrile, or polyvinylidene fluoride ultrafiltration membrane with a molecular weight cutoff of 20,000 to 150,000 Da.
[0020] Further, in step S2, the concentration of the densification-inducing ion solution is 0.01~3 mol / L.
[0021] Furthermore, the solution of the densification-induced ions is weakly acidic, neutral, or weakly alkaline.
[0022] Furthermore, in step S2, the heat treatment temperature is 30~90℃ and the heat treatment time is 1~30 min.
[0023] Secondly, the present invention provides a highly permeable selective nanofiltration membrane prepared according to the above method.
[0024] Furthermore, within a temperature range of 30–90°C, the high-permeability selective nanofiltration membrane exhibits a Na₂SO₄ rejection rate decrease of less than 5% and a pure water flux change rate of less than 15%. After continuous operation at 70°C for 100 hours, the separation performance of the high-permeability selective nanofiltration membrane decreases by less than 8%, demonstrating excellent temperature stability. The high-permeability selective nanofiltration membrane exhibits a Na₂SO₄ rejection rate ≥99%, a NaCl rejection rate ≤50%, and a pure water flux ≥20. .
[0025] Thirdly, this invention also provides an application of the high-permeability selective nanofiltration membrane prepared according to the above method in the separation of materials at high temperatures. Compared with the prior art, this invention has the following outstanding advantages:
[0026] (1) Pion-induced post-treatment strategy: For the first time, the characteristics of strongly hydrated ions in the Hofmeister effect were introduced into the post-treatment modification of polyamide nanofiltration membranes, and the structure-activity relationship between ion types, chain segment interactions, membrane microstructure and macroscopic properties was established, providing new theoretical guidance for the precise preparation of high-performance nanofiltration membranes.
[0027] (2) Achieving "dense-high flux" synergy: Through ion-induced ordered densification, while improving the rejection rate, the flux can be maintained or even increased by 10-20% compared with traditional hydrothermal treatment, breaking through the bottleneck of flux loss in traditional heat treatment and achieving synergistic optimization of permeability and selectivity; the prepared nanofiltration membrane has excellent permeability selectivity, with a rejection rate of ≥99% for Na2SO4, a rejection rate of ≤50% for NaCl, and a pure water flux of ≥20. ;
[0028] (3) Significantly improved temperature resistance: The regular chain segment arrangement and enhanced inter-chain interaction effectively suppress the thermal motion of chain segments at high temperatures; the membrane’s rejection rate of Na2SO4 decreases by less than 5% and the change rate of pure water flux is less than 15% in the temperature range of 25~85℃; after running continuously at 80℃ for 100 hours, the separation performance decay rate is less than 8%, showing excellent temperature resistance stability and broadening the application prospects of nanofiltration membranes in the field of high temperature material treatment;
[0029] (4) Simple process and easy to scale up: The method of the present invention only requires adding a water bath soaking step after the conventional interface polymerization process. It does not require changing the existing production line, introducing organic solvents or complex equipment, and has a wide operating window (temperature 40~95℃, concentration 0.01~3 mol / L), making it easy to implement in industrial applications.
[0030] (5) Wide range of ion selection and flexible control: By selecting different types of inorganic / organic ions and their concentration combinations, the membrane pore size can be precisely controlled in the range of 0.25~0.60 nm to meet different separation requirements. Attached Figure Description
[0031] Figure 1 The graph shows the effect of different heat treatment methods and ion types on the water flux of nanofiltration membranes.
[0032] Figure 2 The graph shows the effect of different heat treatment methods and ion types on the salt rejection rate of nanofiltration membranes.
[0033] Figure 3 The graph shows the effect of different NaF concentrations on the water flux and Na2SO4 rejection rate of the nanofiltration membrane.
[0034] Figure 4 The graph shows the effect of different water bath temperatures on the water flux and Na2SO4 rejection rate of the nanofiltration membrane.
[0035] Figure 5 This is a graph showing the long-term operational stability test of the nanofiltration membrane. Detailed Implementation
[0036] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] It should be noted that, unless otherwise specified, the features in the following embodiments and implementation methods can be combined with each other.
[0038] Firstly, this invention proposes a method for preparing a highly permeable and selective nanofiltration membrane. The principle of this method is as follows: Utilizing the Hofmeister effect in the regulation of protein structure by inorganic salts, and based on the property of strongly hydrated ions to regulate protein hydration structure and induce chain rearrangement, these ions are introduced into the post-interfacial polymerization treatment of polyamide nanofiltration membranes. Densification-inducing ions with strong hydrogen bond acceptor or coordination capabilities specifically interact with nascent polyamide chains under mild hot water bath conditions. This interaction enhances the physical cross-linking points between chains by forming hydrogen bond bridges or ion-dipole coordination bonds, regulating the microphase separation behavior of the membrane separation layer, and inducing controllable contraction and ordered rearrangement of the chains. This fills the free volume defects in the nascent membrane, forming a dense and thermally stable separation layer structure. Simultaneously, this ion-induced rearrangement process promotes the orderly interconnection of hydrophilic microregions within the membrane, reducing the resistance to water molecule transport, thereby maintaining or even increasing water flux while improving the rejection rate.
[0039] The method for preparing the high-permeability selective nanofiltration membrane includes the following steps:
[0040] (1) Interfacial polymerization reaction was carried out on the surface of the base film using a polyamine aqueous solution and a polyacrylamide oil solution to obtain a nascent polyamide film.
[0041] The interfacial polymerization reaction conditions are as follows: aqueous phase immersion time of 120 seconds and oil phase reaction time of 100 seconds. The polyamine aqueous phase solution and the polyacrylamide chloride oil phase solution are prepared separately from the polyamine aqueous phase monomer and the polyacrylamide chloride oil phase monomer: the polyamine aqueous phase monomer includes piperazine, polyethyleneimine, and m-phenylenediamine, with a concentration of 0.05~3 wt%; the polyacrylamide chloride oil phase monomer includes trimesoyl chloride and isophthaloyl chloride, with a concentration of 0.05~1 wt%; the mass ratio of the polyamine aqueous phase monomer to the polyacrylamide chloride oil phase monomer is 0.05~60. The base membrane is a polysulfone, polyethersulfone, polyacrylonitrile, or polyvinylidene fluoride ultrafiltration membrane with a molecular weight cutoff of 20,000~150,000 Da.
[0042] (2) The nascent polyamide membrane obtained in step (1) is placed in an aqueous solution containing densification-inducing ions for heat treatment to obtain a heat-treated composite membrane; wherein, the densification-inducing ions include inorganic anions, organic anions, and cations; the inorganic anions include , , , The organic anions include formate ( ), acetate ( ), propionate ( ), citrate ( ), tartrate ( The cation includes: , , , , The concentration of the densification-inducing ions in the solution is 0.01~3 mol / L, the heat treatment temperature is 30~90℃, and the heat treatment time is 1~30 min.
[0043] (3) The composite membrane after heat treatment is cleaned and dried to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0044] It should be noted that the inorganic anions, organic anions, and cations mentioned have strong hydrogen bond acceptor or strong coordination ability, and all have similar membrane performance regulation capabilities, and can all be used to complete the present invention; in the embodiments of the present invention, some ion types were selected for actual testing, and the scope of protection of the present invention is not limited to the embodiments, but includes all ion types mentioned in the above steps.
[0045] The polyamine aqueous monomers mentioned are all monomer materials commonly used in the preparation of nanofiltration membranes by interfacial polymerization, and have similar interfacial polymerization film-forming capabilities, and can all be used to complete this invention.
[0046] The polyacyl chloride oil phase monomers include pyromellitic trimethylol chloride and isophthaloyl chloride, both of which are commonly used monomer materials for interfacial polymerization to prepare nanofiltration membranes. They have similar interfacial polymerization membrane-forming capabilities and can both be used to complete this invention.
[0047] The base membrane types mentioned are all commonly used base membrane materials for preparing nanofiltration membranes through interfacial polymerization, and they have similar interfacial polymerization film-forming capabilities, so they can all be used to complete this invention. Base membranes with a molecular weight cut of 20,000~150,000 Da can all be used to complete this invention.
[0048] Secondly, the present invention provides a high-permeability selective nanofiltration membrane obtained by the above preparation method.
[0049] Thirdly, the present invention provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0050] Comparative Example 1 (Conventional interfacial polymer film, no post-treatment)
[0051] A polyethersulfone ultrafiltration membrane (molecular weight cutoff 150,000 Da) was used as the base membrane. A 0.05 wt% piperazine aqueous solution and a 0.25 wt% trimesoyl chloride-hexane oil solution were prepared, with a water / oil monomer ratio of 0.2. The base membrane was immersed in the aqueous solution for 120 seconds, removed to remove excess droplets, and then immersed in the oil solution for 100 seconds to prepare a nascent polyamide membrane. The nascent polyamide membrane was then thoroughly washed and soaked in deionized water to obtain a membrane without heat treatment, denoted as NF-Control.
[0052] Comparative Example 2 (Pure Water Bath Heat Treatment)
[0053] A polyethersulfone ultrafiltration membrane (molecular weight cutoff 150,000 Da) was used as the base membrane. A 0.05 wt% piperazine aqueous solution and a 0.25 wt% trimesoyl chloride-hexane oil solution were prepared, with a water / oil monomer ratio of 0.2. The base membrane was immersed in the aqueous solution for 120 seconds, removed to remove excess droplets, and then immersed in the oil solution for 100 seconds to prepare the nascent polyamide membrane. The nascent composite membrane was then heat-treated in a 50°C deionized water bath for 10 minutes, followed by washing with deionized water and storage. The resulting membrane is designated NF-HotWater.
[0054] Example 1
[0055] This embodiment uses inorganic anion NaF for treatment.
[0056] In a first aspect, this embodiment proposes a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0057] (1) A nascent polyamide membrane was obtained by interfacial polymerization of a polyamine aqueous solution and a polyacrylamide chloride oil solution on the surface of the base membrane. In this embodiment, a polyethersulfone ultrafiltration membrane (with a molecular weight cut of 150,000 Da) was used as the base membrane, piperazine was used as the aqueous monomer, and trimesoyl chloride was used as the oil monomer. 0.05 wt% of piperazine aqueous solution and 0.25 wt% of trimesoyl chloride n-hexane oil solution were prepared respectively, and the mass of water / oil monomer was 0.2.
[0058] The interfacial polymerization reaction is specifically as follows: the base film is immersed in a polyamine aqueous solution for 120 seconds, removed to remove excess droplets from the surface, and then immersed in a polyacrylamide chloride oil solution for 100 seconds to prepare a nascent polyamide film.
[0059] (2) The nascent polyamide membrane was then placed in a 50°C water bath containing 0.1 mol / L sodium fluoride (NaF) for 10 min to obtain the heat-treated composite membrane.
[0060] (3) After taking out the heat-treated composite membrane, wash it thoroughly with deionized water to remove residual salt ions on the membrane surface and dry it to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0061] Secondly, this embodiment provides a high-permeability selective nanofiltration membrane obtained by the above method. The membrane obtained in this embodiment is denoted as NF-F. - .
[0062] Thirdly, this embodiment provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0063] Example 2
[0064] This embodiment uses inorganic anion NaF for treatment.
[0065] In a first aspect, this embodiment proposes a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0066] (1) A nascent polyamide membrane was obtained by interfacial polymerization of a polyamine aqueous solution and a polyacrylamide chloride oil solution on the surface of the base membrane. In this embodiment, a polyethersulfone ultrafiltration membrane (with a molecular weight cut of 150,000 Da) was used as the base membrane, piperazine was used as the aqueous monomer, and trimesoyl chloride was used as the oil monomer. A 0.05 wt% aqueous solution of piperazine and a 1.00 wt% hexane oil solution of trimesoyl chloride were prepared respectively, and the mass ratio of water to oil monomer was 0.05.
[0067] The interfacial polymerization reaction is specifically as follows: the base film is immersed in a polyamine aqueous solution for 120 seconds, removed to remove excess droplets from the surface, and then immersed in a polyacrylamide chloride oil solution for 100 seconds to prepare a nascent polyamide film.
[0068] (2) The nascent polyamide membrane was then placed in a 50°C water bath containing 0.1 mol / L sodium fluoride (NaF) for 10 min to obtain the heat-treated composite membrane.
[0069] (3) After taking out the heat-treated composite membrane, wash it thoroughly with deionized water to remove residual salt ions on the membrane surface and dry it to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0070] Secondly, this embodiment provides a high-permeability selective nanofiltration membrane obtained by the above method. The membrane obtained in this embodiment is denoted as NF-F. - / 0.05.
[0071] Thirdly, this embodiment provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0072] Example 3
[0073] This embodiment uses inorganic anion NaF for treatment.
[0074] In a first aspect, this embodiment proposes a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0075] (1) Interfacial polymerization reaction was carried out on the surface of the base membrane using a polyamine aqueous solution and a polyacrylamide oil solution to obtain a nascent polyamide membrane. In this embodiment, a polyethersulfone ultrafiltration membrane (with a molecular weight cut of 150,000 Da) was used as the base membrane, piperazine was used as the aqueous monomer, and trimesoyl chloride was used as the oil monomer. A 0.6 wt% aqueous solution of piperazine and a 0.01 wt% hexane oil solution of trimesoyl chloride were prepared respectively, with a water / oil monomer mass ratio of 60.
[0076] The interfacial polymerization reaction is specifically as follows: the base film is immersed in a polyamine aqueous solution for 120 seconds, removed to remove excess droplets from the surface, and then immersed in a polyacrylamide chloride oil solution for 100 seconds to prepare a nascent polyamide film.
[0077] (2) The nascent polyamide membrane was then placed in a 50°C water bath containing 0.1 mol / L sodium fluoride (NaF) for 10 min to obtain the heat-treated composite membrane.
[0078] (3) After taking out the heat-treated composite membrane, wash it thoroughly with deionized water to remove residual salt ions on the membrane surface and dry it to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0079] Secondly, this embodiment provides a high-permeability selective nanofiltration membrane obtained by the above method. The membrane obtained in this embodiment is denoted as NF-F. - / 60.
[0080] Thirdly, this embodiment provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0081] Example 4
[0082] This embodiment uses inorganic anion Na2SO4 for treatment.
[0083] In a first aspect, this embodiment proposes a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0084] (1) A nascent polyamide membrane was obtained by interfacial polymerization of a polyamine aqueous solution and a polyacrylamide chloride oil solution on the surface of the base membrane. In this embodiment, a polyethersulfone ultrafiltration membrane (with a molecular weight cut of 150,000 Da) was used as the base membrane, piperazine was used as the aqueous monomer, and trimesoyl chloride was used as the oil monomer. A 0.05 wt% aqueous solution of piperazine and a 0.25 wt% hexane oil solution of trimesoyl chloride were prepared respectively, and the mass ratio of water to oil monomer was 0.2.
[0085] The interfacial polymerization reaction is specifically as follows: the base film is immersed in a polyamine aqueous solution for 120 seconds, removed to remove excess droplets from the surface, and then immersed in a polyacrylamide chloride oil solution for 100 seconds to prepare a nascent polyamide film.
[0086] (2) The nascent polyamide membrane was then placed in a 50°C water bath containing 0.3 mol / L sodium acetate (CH3COONa) for 10 min to obtain the heat-treated composite membrane.
[0087] (3) After taking out the heat-treated composite membrane, wash it thoroughly with deionized water to remove residual salt ions on the membrane surface and dry it to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0088] Secondly, this embodiment provides a high-permeability selective nanofiltration membrane obtained by the above method. The membrane obtained in this embodiment is denoted as NF- .
[0089] Thirdly, this embodiment provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0090] Example 5
[0091] This embodiment uses organic anionic sodium acetate for treatment.
[0092] The difference from Example 1 is that the salt in the heat treatment water bath was replaced with 0.3 mol / L sodium acetate (CH3COONa). The resulting membrane is designated as NF-CH3COO. - .
[0093] In a first aspect, this embodiment proposes a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0094] (1) A nascent polyamide membrane was obtained by interfacial polymerization of a polyamine aqueous solution and a polyacrylamide chloride oil solution on the surface of the base membrane. In this embodiment, a polyethersulfone ultrafiltration membrane (with a molecular weight cut of 150,000 Da) was used as the base membrane, piperazine was used as the aqueous monomer, and trimesoyl chloride was used as the oil monomer. A 0.05 wt% aqueous solution of piperazine and a 0.25 wt% hexane oil solution of trimesoyl chloride were prepared respectively, and the mass ratio of water to oil monomer was 0.2.
[0095] The interfacial polymerization reaction is specifically as follows: the base film is immersed in a polyamine aqueous solution for 120 seconds, removed to remove excess droplets from the surface, and then immersed in a polyacrylamide chloride oil solution for 100 seconds to prepare a nascent polyamide film.
[0096] (2) The nascent polyamide membrane was then placed in a 50°C water bath containing 0.3 mol / L sodium acetate (CH3COONa) for 10 min to obtain the heat-treated composite membrane.
[0097] (3) After taking out the heat-treated composite membrane, wash it thoroughly with deionized water to remove residual salt ions on the membrane surface and dry it to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0098] Secondly, this embodiment provides a high-permeability selective nanofiltration membrane obtained by the above method. The membrane obtained in this embodiment is denoted as NF-CH3COO. - .
[0099] Thirdly, this embodiment provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0100] Example 6
[0101] This embodiment uses cationic LiCl treatment.
[0102] In a first aspect, this embodiment proposes a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0103] (1) A nascent polyamide membrane was obtained by interfacial polymerization of a polyamine aqueous solution and a polyacrylamide chloride oil solution on the surface of the base membrane. In this embodiment, a polyethersulfone ultrafiltration membrane (with a molecular weight cut of 150,000 Da) was used as the base membrane, piperazine was used as the aqueous monomer, and trimesoyl chloride was used as the oil monomer. A 0.05 wt% aqueous solution of piperazine and a 0.25 wt% hexane oil solution of trimesoyl chloride were prepared respectively, and the mass ratio of water to oil monomer was 0.2.
[0104] The interfacial polymerization reaction is specifically as follows: the base film is immersed in a polyamine aqueous solution for 120 seconds, removed to remove excess droplets from the surface, and then immersed in a polyacrylamide chloride oil solution for 100 seconds to prepare a nascent polyamide film.
[0105] (2) The nascent polyamide membrane was then placed in a 50°C water bath containing 0.3 mol / L lithium chloride (LiCl) for 10 min to obtain the heat-treated composite membrane.
[0106] (3) After taking out the heat-treated composite membrane, wash it thoroughly with deionized water to remove residual salt ions on the membrane surface and dry it to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0107] Secondly, this embodiment provides a high-permeability selective nanofiltration membrane obtained by the above method. The membrane obtained in this embodiment is denoted as NF-Li. + .
[0108] Thirdly, this embodiment provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0109] Example 7
[0110] This embodiment uses cationic CaCl2 treatment.
[0111] In a first aspect, this embodiment proposes a method for preparing a highly permeable and selective nanofiltration membrane, comprising the following steps:
[0112] (1) A nascent polyamide membrane was obtained by interfacial polymerization of a polyamine aqueous solution and a polyacrylamide chloride oil solution on the surface of the base membrane. In this embodiment, a polyethersulfone ultrafiltration membrane (with a molecular weight cut of 150,000 Da) was used as the base membrane, piperazine was used as the aqueous monomer, and trimesoyl chloride was used as the oil monomer. A 0.05 wt% aqueous solution of piperazine and a 0.25 wt% hexane oil solution of trimesoyl chloride were prepared respectively, and the mass ratio of water to oil monomer was 0.2.
[0113] The interfacial polymerization reaction is specifically as follows: the base film is immersed in a polyamine aqueous solution for 120 seconds, removed to remove excess droplets from the surface, and then immersed in a polyacrylamide chloride oil solution for 100 seconds to prepare a nascent polyamide film.
[0114] (2) The nascent polyamide membrane was then placed in a 50°C water bath containing 0.3 mol / L calcium chloride (CaCl2) for 10 min to obtain the heat-treated composite membrane.
[0115] (3) After taking out the heat-treated composite membrane, wash it thoroughly with deionized water to remove residual salt ions on the membrane surface and dry it to obtain a nanofiltration membrane with both high permeability selectivity and excellent temperature resistance.
[0116] Secondly, this embodiment provides a high-permeability selective nanofiltration membrane obtained by the above method. The membrane obtained in this embodiment is denoted as NF-Ca. 2+ .
[0117] Thirdly, this embodiment provides an application of the above-mentioned high-permeability selective nanofiltration membrane in the separation of high-temperature materials.
[0118] Example 8
[0119] This example is a concentration optimization experiment.
[0120] Polyethersulfone ultrafiltration membrane (molecular weight cut to 150,000 Da) was used as the base membrane. A 0.05 wt% piperazine aqueous solution and a 0.25 wt% trimesoyl chloride-hexane oil solution were prepared, with a water / oil monomer ratio of 0.2. The base membrane was immersed in the aqueous solution for 120 seconds, removed to remove excess droplets, and then immersed in the oil solution for 100 seconds to prepare a nascent polyamide membrane. The nascent composite membrane was then heat-treated for 10 min in a 50°C water bath containing different concentrations of sodium fluoride (NaF). The sodium fluoride concentrations were 0.05 mol / L, 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, and 1.0 mol / L, respectively, to investigate the effect of sodium fluoride concentration on membrane performance.
[0121] Example 9
[0122] This example is a temperature optimization experiment.
[0123] A polyethersulfone ultrafiltration membrane (molecular weight cutoff 150,000 Da) was used as the base membrane. A 0.05 wt% piperazine aqueous solution and a 0.25 wt% trimesoyl chloride-hexane oil solution were prepared, with a water / oil monomer ratio of 0.2. The base membrane was immersed in the aqueous solution for 120 seconds, removed to remove excess droplets, and then immersed in the oil solution for 100 seconds to prepare a nascent polyamide membrane. Subsequently, the nascent composite membrane was placed in a 0.3 mol / L sodium fluoride (NaF) aqueous solution and heat-treated for 10 min at different water bath temperatures: 30℃, 50℃, 70℃, and 90℃, to investigate the effect of temperature on membrane performance.
[0124] Example 10
[0125] This example is a long-term operational stability test.
[0126] The NF-F membrane prepared in Example 1 was continuously operated at 70°C and 0.6 MPa for 100 h, and its rejection rate and flux of Na2SO4 were monitored. Then, the membrane performance was characterized and evaluated.
[0127] The prepared nanofiltration membrane was subjected to the following performance tests:
[0128] Permeation flux: The pure water flux was measured at a pressure of 0.6 MPa and a temperature of 25°C.
[0129] Retention performance: The retention rates for 2000 ppm Na₂SO₄ and NaCl were determined respectively. Retention rate R = (1 - C p / C f ) × 100%, where C p and C f These are the conductivity of the permeate and the feed liquid, respectively.
[0130] Pore size distribution: The molecular weight cutoff curve was determined by neutral molecule cutoff, and the average pore size and pore size distribution were calculated.
[0131] Temperature resistance: The membrane’s rejection rate and flux change for Na2SO4 were measured in the temperature range of 30~90℃.
[0132] Long-term stability: The system was continuously operated at 70℃ and 0.6 MPa for 100 h, and the performance degradation was monitored.
[0133] Table 1. Effects of different densification-inducing ions on nanofiltration membrane performance
[0134]
[0135] Results analysis:
[0136] As shown in Table 1, the temperature resistance of the membranes was significantly improved after treatment with different types of densification-induced ions. Among them, the membrane of Example 1 (NaF treatment) exhibited the best overall performance: the pure water flux reached 22.5 LMH / bar, which was 58.5% higher than that of Comparative Example 2 (e.g., ...). Figure 1 As shown); the Na2SO4 rejection rate reached 99.6%, an improvement of 13.4% compared to Comparative Example 2; meanwhile, the NaCl rejection rate remained at a low level of 38.5%, demonstrating good monovalent / multivalent ion selectivity (e.g. Figure 2 (As shown). In the 70℃ high-temperature test, the flux decay rate of the NF-F membrane was only 12%, and the retention rate decay was only 1.5%, which is far better than Comparative Example 2 (flux decay of 25% and retention rate decay of 4.8%), verifying the significant improvement effect of the method of the present invention on the temperature resistance performance. This result confirms the mechanism of action of the present invention: As a strong hydrogen bond acceptor, it can penetrate into the polyamide network and form hydrogen bond bridges with NH groups, enhancing the physical cross-linking points between chains. Under the synergistic effect of heating in a 50°C water bath, the chain segments rearrange into an ordered conformation at a lower energy state, filling the free volume defects in the nascent membrane and achieving structural densification. At the same time, the rearrangement process promotes the orderly interconnection of hydrophilic microregions, reducing the resistance to water molecule transport, thereby maintaining a high flux while increasing the rejection rate. When the water / oil phase ratio is adjusted from 0.2 to 0.05, the membrane densification control effect weakens, because the separation layer is relatively loose under low water / oil phase ratio conditions. When it is further increased to 60, the separation layer becomes more dense, and the introduction of fluoride ions further improves the membrane density, with a sodium sulfate rejection rate of 99.8%.
[0137] Table 2 Results of Example 8 (NaF Concentration Optimization)
[0138]
[0139] Table 2 shows that as the NaF concentration increases from 0 to 0.3 mol / L, the membrane flux and rejection rate increase simultaneously, while the pore size decreases and the pore size distribution narrows, indicating that F... - Induced ordered compaction was dominant. When the concentration exceeded 0.3 mol / L, the rejection rate continued to increase slightly, but the flux began to decrease, indicating that excessive compaction led to channel blockage (e.g., Figure 3 (As shown). Therefore, 0.1~0.5 mol / L is the preferred concentration range, and 0.3 mol / L is the optimal concentration.
[0140] Table 3 Results of Example 9 (Optimization of Heat Treatment Temperature)
[0141]
[0142] Table 3 shows that the optimal overall performance is obtained within a heat treatment temperature range of 50~70℃. At excessively low temperatures, chain segment movement is insufficient, F - The induced rearrangement effect is limited; at excessively high temperatures (90℃), the thermal motion of chain segments is too strong, which may destroy F. - The guided ordered structure leads to a slight decrease in flux (e.g.) Figure 4 (As shown).
[0143] Table 4 Results of Example 10 (Long-term operational stability)
[0144]
[0145] As shown in Table 4, the NF-F prepared in Example 1 - After 100 hours of continuous operation at 70℃ and 0.6 MPa, the membrane maintained a Na₂SO₄ rejection rate of over 98.8% and a flux decline rate of less than 5%, demonstrating excellent temperature-resistant operational stability. This result further confirms... The induced ordered rearrangement structure has good thermal stability (e.g. Figure 5 (As shown).
[0146] This invention does not introduce additional nanomaterials, alter the monomer system, or add an intermediate layer. Instead, it introduces specific ions during the heat treatment stage after interfacial polymerization. Utilizing the hydrogen bonding or coordination interactions between these ions and polyamide segments, it gently induces controllable densification and ordered rearrangement of the formed membrane. This method improves the membrane's temperature resistance while maintaining or even increasing water flux. Furthermore, the process is simple and requires no changes to existing production lines, providing a novel technological pathway for the preparation of high-performance temperature-resistant nanofiltration membranes.
[0147] Other embodiments of this application will readily occur to those skilled in the art upon consideration of the specification and practice of the disclosure herein. This application is intended to cover any variations, uses, or adaptations of this application that follow the general principles of this application and include common knowledge or customary techniques in the art not disclosed herein. The specification and embodiments are to be considered exemplary only.
[0148] It should be understood that this application is not limited to the precise structure described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope.
Claims
1. A method for preparing a high-permeability selective nanofiltration membrane, characterized in that, Includes the following steps: S1: An interfacial polymerization reaction is carried out on the surface of the base film using a polyamine aqueous solution and a polyacrylamide oil solution to form a nascent polyamide film; S2: The nascent polyamide membrane is placed in an aqueous solution containing densification-inducing ions for heat treatment to obtain a heat-treated composite membrane; the aqueous solution containing densification-inducing ions is an aqueous solution containing sodium fluoride, sodium sulfate, sodium acetate, lithium chloride, or calcium chloride; the heat treatment temperature is 30~90℃, and the heat treatment time is 1~30 min; the concentration of the aqueous solution containing densification-inducing ions is 0.01~3 mol / L; S3: After heat treatment, the composite membrane is cleaned and dried to obtain a high-permeability selective nanofiltration membrane.
2. The method according to claim 1, characterized in that, In step S1, the polyamine aqueous solution and the polyacrylamide oil solution are prepared by the polyamine aqueous monomer and the polyacrylamide oil monomer, respectively. The polyamine aqueous monomer includes piperazine, polyethyleneimine, and m-phenylenediamine; the polyacrylamide oil monomer includes pyromellitic tricarboxylic acid chloride and isophthaloyl chloride.
3. The method according to claim 2, characterized in that, The mass ratio of the aqueous phase monomer of the polyamine to the oil phase monomer of the polyacrylamide chloride is 0.05~60.
4. The method according to claim 1, characterized in that, In step S1, the base membrane is a polysulfone, polyethersulfone, polyacrylonitrile, or polyvinylidene fluoride ultrafiltration membrane with a molecular weight cutoff of 20,000 to 150,000 Da.
5. The method according to claim 1, characterized in that, The aqueous solution containing densification-inducing ions is weakly acidic, neutral, or weakly alkaline.
6. A high-permeability selective nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 5.
7. The high-permeability selective nanofiltration membrane according to claim 6, characterized in that, Within a temperature range of 30–90°C, the high-permeability selective nanofiltration membrane exhibits a Na₂SO₄ rejection rate decrease of less than 5% and a pure water flux change rate of less than 15%. After continuous operation at 70°C for 100 hours, the separation performance of the high-permeability selective nanofiltration membrane decreases by less than 8%, demonstrating excellent temperature stability. The high-permeability selective nanofiltration membrane exhibits a Na₂SO₄ rejection rate ≥99%, a NaCl rejection rate ≤50%, and a pure water flux ≥20. .
8. The application of a high-permeability selective nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 5 in the separation of high-temperature materials.
Citation Information
Patent Citations
High-temperature-resistant composite nanofiltration membrane and preparation method thereof
CN115672031A
High-temperature-resistant nanofiltration membrane based on nanometer material middle layer as well as preparation method and application of high-temperature-resistant nanofiltration membrane
CN116899419A
A high temperature resistant nanofiltration membrane reinforced by halloysite nanotubes and its preparation method and application
CN118371134B
High-temperature-resistant nanofiltration membrane based on rigid amine monomer as well as preparation method and application of high-temperature-resistant nanofiltration membrane
CN118491316A
A high-temperature resistant nanofiltration membrane and its preparation method
CN119588179B